Cystic adventitial degeneration of the popliteal artery - Keese, Michael; Diehl, Steffen J.; Huck, Kurt; Ströbel, Philipp; Schönberg, Stefan; Niedergethmann, Marco (Annals of vascular surgery, 2012)
Cystic adventitial degeneration (CAD) of the popliteal artery is a rare, but well-recognized, disorder leading to claudication. Usually, surgical treatment is indicated. So far, <400 patients have been described. We report on a series of three patients with CAD. Because we observed local recurrence of CAD after local resection, we conclude that 360° resection and venous interposition is preferable for a favorable outcome. Furthermore, we review etiology, pathology, and different surgical treatment approaches.